Multifactorial diffusion of chloride Ions in concrete considering the non-linear voltage distortion of other species - Zacchei, Enrico; Lizarazo Marriaga, Juan; García-Sánchez, Felipe; Tadeu, Antonio (Springer, 2023)
One of the most relevant deterioration mechanisms of reinforced concrete (RC) structures is the corrosion of steel bars by chloride ions. The service life of structures could be extended by monitoring this process. The lack of correlation data between chloride ion diffusion and the electrical ﬁeld has meant that alternative methods have been developed in this paper. One such method considers diffusivity and the electrical ﬁeld as non-constant, although they are usually assumed constant, that is, without there being any variability of the involved factors. Therefore, a multi-factorial diffusivity that accounts for the material characteristics and environmental variations is adopted. In addition, an innovative stochastic approach to evaluate the variation of the electrical ﬁeld while accounting for the non-linear voltage distortion, which considers a multispecies model, has been proposed. More complete 1D/2D electro-mechanical models that are solved by advanced numerical and analytical solutions for electro-mechanical diffusion have been developed. Results show that spatiotemporal numerical models estimate the chloride concentration well, estimating more reliable scenarios to provide information on the safety situation of the structure and make it more sustainable by employing successful preventive treatments.
Keywords: Hormigón armado - Deterioro; Chloride diffusion; Non-constant electric ﬁeld; Multi-factorial diffusivity; Self-diffusion; Multi-species models